Biblioteka klasztoru paulinów w Oporowie w świetle zachowanych katalogów z XVIII wieku - Sukiennik, Edgar (Saeculum Christianum. Pismo Historyczne, 2019)
From the very beginning of its existence, the Pauline Order paid attention to the need to educate and develop the intellectual life of its members. This resulted from the adoption of St. Augustine’s rule by the community, which in addition to the principles governing the common life also emphasized the intellectual formation of the friars by providing them with access to books. The fulfilment of the obligations resulting from the rule and the subsequent legislation of the convent meant that every Pauline monastery was equipped with a larger or smaller library. It was no different in the case of St. Martin's convent in Oporów, which had existed since 1453 thanks to the foundation of the brothers Piotr and Władysław from the powerful Oporowski family, with the Sulima coat of arms. The monastery library was probably established soon after the foundation of the monastery. It was used primarily by preachers, who prepared Sunday and Christmas sermons, as well as by other monks, if they were authorized to do so. The beginnings of the library are unknown due to the lack of sources from that period. Only the eighteenth-century catalogues of books shed light on the functioning of the library, albeit in a limited period of time 1711-1753. To this day, 13 library inventories have survived, providing welcome information about the intellectual life of the local Pauline monks, titles of books along with the names of the authors and the division of bibliographic material into various thematic categories. The image of the Oporów library is complemented by 47 old prints of Oporów provenience, which are now the property of the University Library in Warsaw. Although their number is insignificant and constitutes only a fraction of the former assets of the library, nevertheless it turns out to be helpful in the analysis of the resources of the Pauline library and the development of intellectual horizons of its users. The analysis of the preserved archival materials is the first attempt to restore the library of the Oporów monastery in the century preceding its irretrievable disappearance in the course of the convent’s annulment.